Price Reform and Durable Goods in the Transition to a Market Economy - Agenor, Pierre-Richard (IMF Working Papers; Working Paper ;, 1993)
The paper examines the short- and long-term effects of price liberalization in a reforming socialist economy. The analysis is based on an optimizing framework that highlights hoarding behavior and the existence of parallel goods markets. The behavior of official and parallel market prices, stock of durables, and the velocity of money in the transition period between reform announcement and reform implementation is characterized, in the presence and absence of uncertainty about the transition date.